Increased autologous blood donation in rectal cancer by recombinant human erythropoietin (rhEPO) - Rau, Beate; Schlag, Peter M.; Willeke, Frank; Herfarth, Christian; Stephan, P.; Franke, W. (European journal of cancer, 1998)
A randomised, placebo-controlled trial was conducted to study whether the subcutaneous administration of recombinant human erythropoietin (rhEPO) increases the donated red cell blood volume in patients with rectal cancer. Patients with resectable rectal cancer and a haemoglobin (Hb) level ≥12.5/>12g/dl (males/females) were scheduled to receive pre-operatively either erythropoietin (200U/kg body weight daily) (n=28) or placebo (n=26) subcutaneously for 11 days. During this period autologous blood was collected. No serious adverse events were attributed to erythropoietin. 20 of 28 patients treated with rhEPO were able to donate ≥3 units (71%) compared with 11 of 26 control patients (42%). The mean cumulative volume of red cells donated was 29% higher in the patients who received rhEPO (571 versus 444ml, P=0.02). The change in the mean reticulocyte value from baseline to the last pre-operative value was significantly higher in the rhEPO group (10.4 to 61.6‰ versus 11.0 to 20.1‰, P=0.0001). The fall in the mean haematocrit from baseline to the last pre-operative value was significantly lower in the rhEPO group (41.4 to 37.6% versus 41.8 to 34.8%, P=0.0004). rhEPO increases the ability of cancer patients to donate autologous blood during a short pre-operative period and enhances the restoration of haematological values after the donation period.